Calculation:

In \(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\)

\(\displaystyle\angle{B}{A}{C}=\angle{D}{E}{F}\) (Given)

\(\displaystyle\angle{A}{C}{B}=\angle{E}{D}{F}\) (Vertically opposite angle)

\(\displaystyle\angle{B}{A}{C}=\angle{D}{F}{E}\) (By properties of triangle)

\(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\) are similar.

In \(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\)

\(\displaystyle\angle{B}{A}{C}=\angle{D}{E}{F}\) (Given)

\(\displaystyle\angle{A}{C}{B}=\angle{E}{D}{F}\) (Vertically opposite angle)

\(\displaystyle\angle{B}{A}{C}=\angle{D}{F}{E}\) (By properties of triangle)

\(\displaystyle\triangle{A}{B}{C}{\quad\text{and}\quad}\triangle{D}{E}{F}\) are similar.